2016
DOI: 10.1103/physrevb.94.214513
|View full text |Cite
|
Sign up to set email alerts
|

Full-gap superconductivity in noncentrosymmetric Re6Zr,Re27Zr5 , and Re24

Abstract: Non-centrosymmetric superconductor Re 6 Zr has attracted much interest, for its possible unconventional superconducting state with time reversal symmetry broken. Here we report the 185/187 Re nuclear quadrupole resonance (NQR) measurements on Re 6 Zr (T c = 6.72 K) and the isostructural compounds Re 27 Zr 5 (T c = 6.53 K) and Re 24 Zr 5 (T c = 5.00 K). The nuclear spin-lattice relaxation rate 1/T 1 shows a coherence peak below T c and decreases exponentially at low temperatures in all three samples. The superc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…A more complete understanding of the hyperfine term is required to make any further progress with this analysis. Nuclear quadrupole measurements have also been performed on Re 6 Zr and provide further evidence of a conventional BCS gap symmetry [50].…”
Section: Superconducting Gapmentioning
confidence: 98%
“…A more complete understanding of the hyperfine term is required to make any further progress with this analysis. Nuclear quadrupole measurements have also been performed on Re 6 Zr and provide further evidence of a conventional BCS gap symmetry [50].…”
Section: Superconducting Gapmentioning
confidence: 98%
“…In all cases, the TRS breaking is manifested by the increase of σ ZF below T c . Moreover, while some studies have found evidence for two-gap superconductivity in ReX 126,127 , most measurements were generally well accounted for by a single gap s-wave model [114][115][116][123][124][125][128][129][130][131][132][133][134] . An example of this is displayed in Fig.…”
Section: Noncentrosymmetric La7x3 and Rexmentioning
confidence: 99%
“…For T Zr 4d metal, the α-Mn-type Re 24 Zr 5 (T c 5 K) and Re 6 Zr (T c 6.7 K) have been investigated via both nuclear quadrupole resonance and μSR techniques [17,46]. Except for the α-Mn-type Re-Zr alloys, the MgZn 2 -type Re 2 Zr (similar to hcp-Mg-type) and Mn 21 Zn 25 -type Re 25 Zr 21 have been synthesized [39].…”
Section: Re-based Superconductorsmentioning
confidence: 99%